2023
DOI: 10.1021/jacs.3c08205
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Free Exponential Amplification via Growth and Scission of Crisscross Ribbons from Single-Stranded DNA Components

Anastasia Ershova,
Dionis Minev,
F. Eduardo Corea-Dilbert
et al.

Abstract: The self-assembly of DNA-based monomers into higher-order structures has significant potential for realizing various biomimetic behaviors including algorithmic assembly, ultrasensitive detection, and self-replication. For these behaviors, it is desirable to implement high energetic barriers to undesired spurious nucleation, where such barriers can be bypassed via seed-initiated assembly. Jointneighbor capture is a mechanism enabling the construction of such barriers while allowing for algorithmic behaviors, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We previously demonstrated that crisscross growth could be seeded by a <200 nt target sequence folded into a “nanoseed” mini-origami. , Here, we adapted HypB growth to be seeded by a nanoseed (Figures d and S16), in which nuc-x slats are used to capture a target strand [either a 198-nt section of M13 p8064 or an ultramer oligonucleotide (IDT)] by five segments from their input domains. The output domains of the nuc-x slats share the same sequences as the output domains of the core x-slats so that the core y-slats can be captured by nuc-x slats to initiate HypB growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that crisscross growth could be seeded by a <200 nt target sequence folded into a “nanoseed” mini-origami. , Here, we adapted HypB growth to be seeded by a nanoseed (Figures d and S16), in which nuc-x slats are used to capture a target strand [either a 198-nt section of M13 p8064 or an ultramer oligonucleotide (IDT)] by five segments from their input domains. The output domains of the nuc-x slats share the same sequences as the output domains of the core x-slats so that the core y-slats can be captured by nuc-x slats to initiate HypB growth.…”
Section: Resultsmentioning
confidence: 99%
“…Critically, one target molecule only leads to one ribbon formation, with an ultimate ribbon length of up to ∼10 μm, showing the potential for single-molecule detection. By programming ribbon scission to occur concurrently with growth, we recently expanded isothermal crisscross polymerization from linear to exponential amplification . However, the relatively slow scission limits its application in ultrasensitive detection.…”
Section: Introductionmentioning
confidence: 99%